2017
DOI: 10.1509/jmr.15.0574
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Recycling versus Trashing on Consumption: Theory and Experimental Evidence

Abstract: This article proposes a utilitarian model in which recycling could reduce consumers' negative emotions from wasting resources (i.e., taking more resources than what is being consumed) and increase consumers' positive emotions from disposing of consumed resources. The authors provide evidence for each component of the utility function using a series of choice problems and formulate hypotheses on the basis of a parsimonious utilitarian model. Experiments with real disposal behavior support the model hypotheses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 50 publications
2
61
2
3
Order By: Relevance
“…While some communities are considering a ban with a goal to shift consumption to non-plastic straws, consideration should be given to the impact of moral licensing, which is when we engage in a socially desirable behavior, we tend to ignore the impacts of non-socially desirable behavior. Researchers have found that offering recycling actually increased the consumption of items offered for free as the moral licensing effect made consumption more acceptable (Catlin and Wang, 2013;Sun and Trudel, 2017). If paper and/or compostable straws are provided, with moral licensing, customers tend to feel okay about using and disposing, including littering, of paper and/or compostable straws.…”
Section: Policy Considerationsmentioning
confidence: 99%
“…While some communities are considering a ban with a goal to shift consumption to non-plastic straws, consideration should be given to the impact of moral licensing, which is when we engage in a socially desirable behavior, we tend to ignore the impacts of non-socially desirable behavior. Researchers have found that offering recycling actually increased the consumption of items offered for free as the moral licensing effect made consumption more acceptable (Catlin and Wang, 2013;Sun and Trudel, 2017). If paper and/or compostable straws are provided, with moral licensing, customers tend to feel okay about using and disposing, including littering, of paper and/or compostable straws.…”
Section: Policy Considerationsmentioning
confidence: 99%
“…The main contributions of this paper are as follows: First, while most research on the sharing economy is carried out from the perspective of demand or the consumer, this study is carried out from the perspective of the suppliers. Under the new concepts of "green and sharing development", promoting sustainable development and achieving high-quality growth are the results of reducing resource consumption and improving the recycling of underutilized resources [18]. Unfortunately, the current number of service providers is relatively small.…”
Section: Introductionmentioning
confidence: 99%
“…Third, to promote sustainable development, many scholars have called for a more efficient use of resources [18,19]. The call is mainly manifested in the sharing economy as individuals sharing underutilized resources with others [9,11], but the overall effect is not ideal [6].…”
Section: Introductionmentioning
confidence: 99%
“…Prior work suggests, however, that disposal can provide consumers with a positive way to disengage with their possessions. This includes moving on from the past, de-cluttering (Jacoby et al, 1977;Lastovicka & Fernandez, 2005) or framing their behavior as altruistic, by helping society through disposal (e.g., donation or recycling) (Sun & Trudel, 2017;Ture, 2014;White et al, 2011). The disposal process can shift a negative to a positive, if it offers the right compensation, or effectively alleviates consumer concerns about disposal (Brough & Isaac, 2012;Lastovicka & Fernandez, 2005).…”
Section: Trade-ins With Emotional Rewardmentioning
confidence: 99%
“…Tension arises where a consumer perceives greater value in product ownership, than what they could emotionally or financially gain from product disposal (Bellezza, Ackerman, & Gino, 2017;Okada, 2001). A fundamental premise of past research on product disposal is that while consumers may struggle to give up possessions (Haws et al, 2012;Kleine & Baker, 2004), they are also open to disposal methods that compensate psychological loss with psychological gain (Lastovicka & Fernandez, 2005;Sun & Trudel, 2017;White, MacDonnell, & Dahl, 2011). Consumers have been shown to engage with disposal more willingly, where the action can help others, reduce pollution, or allow them to move on from the past (Jacoby, Berning, & Dietvorst, 1977;Lastovicka & Fernandez, 2005).…”
Section: Introductionmentioning
confidence: 99%